Islet Transplantation Imaging in vivo - Zheng L (Dove Medical Press, 2020)
Lei Zheng1 ,* Yinghao Wang1 ,* Bin Yang1,2 ,* Bo Zhang,1,2 Yulian Wu1,2 1Department of Surgery, The Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou 310000, People’s Republic of China; 2Key Laboratory of Cancer Prevention and Intervention, China National Ministry of Education, Cancer Institute, Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou 310000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bo Zhang; Yulian WuDepartment of Surgery, The Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou 310000, People’s Republic of ChinaTel/ Fax +86 571 87783563Email jjs10@zju.edu.cn; yulianwu@zju.edu.cnAbstract: Although islet transplantation plays an effective and powerful role in the treatment of diabetes, a large amount of islet grafts are lost at an early stage due to instant blood-mediated inflammatory reactions, immune rejection, and β-cell toxicity resulting from immunosuppressive agents. Timely intervention based on the viability and function of the transplanted islets at an early stage is crucial. Various islet transplantation imaging techniques are available for monitoring the conditions of post-transplanted islets. Due to the development of various imaging modalities and the continuous study of contrast agents, non-invasive islet transplantation imaging in vivo has made great progress. The tracing and functional evaluation of transplanted islets in vivo have thus become possible. However, most studies on contrast agent and imaging modalities are limited to animal experiments, and long-term toxicity and stability need further evaluation. Accordingly, the clinical application of the current achievements still requires a large amount of effort. In this review, we discuss the contrast agents for MRI, SPECT/PET, BLI/FI, US, MPI, PAI, and multimodal imaging. We further summarize the advantages and limitations of various molecular imaging methods.Keywords: islet transplantation, imaging modality, non-invasive imaging, multimodal imaging, contrast agent